2004
DOI: 10.1183/09031936.04.00104504
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of emphysema on skeletal muscle fibre atrophy in hamsters

Abstract: Patients afflicted with emphysema demonstrate altered peripheral skeletal muscle fibre composition and atrophy. It is unknown whether these alterations are general to all skeletal muscles independent of function, phenotype or oxidative capacity. Therefore, the purpose of this investigation was to determine whether emphysema induces alterations in muscle fibre composition or atrophy in respiratory and locomotory muscles with diverse fibre types and metabolic profiles.Fibre composition and cross-sectional area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The left gastrocnemius was divided: one portion was saved for morphometric histological procedures, and the other portion was pulverized, frozen in liquid nitrogen and stored at −86°C until used for proteolysis assays.The gastrocnemius muscle has previously been demonstrated as a good indicator of alterations in the skeletal muscle of emphysemic hamsters (Mattson et al . ), including in aspects related to oxidative parameters (Mattson et al . ; Tonon et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The left gastrocnemius was divided: one portion was saved for morphometric histological procedures, and the other portion was pulverized, frozen in liquid nitrogen and stored at −86°C until used for proteolysis assays.The gastrocnemius muscle has previously been demonstrated as a good indicator of alterations in the skeletal muscle of emphysemic hamsters (Mattson et al . ), including in aspects related to oxidative parameters (Mattson et al . ; Tonon et al .…”
Section: Methodsmentioning
confidence: 99%
“…Mattson et al . () demonstrated that emphysema induces fibre atrophy and the response is not specific to locomotory muscles composed of a given fibre‐type or oxidative capacity, in hamsters after 180 days of pulmonary emphysema induced by elastase instillation (25 IU/100 g body weight). Rinaldi et al .…”
mentioning
confidence: 99%
“…The gastrocnemius muscle was excised, weighed, frozen in liquid nitrogen, and stored at −86°C until use. The gastrocnemius muscle has previously been demonstrated as a good indicator of alterations in the skeletal muscle of emphysemic hamsters [22], including those in lipid peroxidation [2]. In hamsters, there is no obvious gross division of fibers in this muscle [23], and therefore, the whole muscle is typically analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…In COPD patients, respiratory muscle weakness and diaphragm fiber atrophy decreases respiratory muscle reserves increasing muscle fatigability/weakness thereby predisposing the patient to chronic hypercapnia [23]. The changes in diaphragm muscle that occur during EMP include muscle fiber shortening by loss of sarcomeres in series [24,25], increase in cross-sectional area of type I and II fibers [26,27], atrophy [28,29] and loss of oxidative enzyme capacity [30]. While the adaptive changes in diaphragm muscle are complex, ultimately EMP augments the energetic requirements of respiratory muscles which, concomitant with EMP-induced reductions in muscle mass, contributes to diaphragm weakness, increased fatigability and overall dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In humans and animals with EMP, changes in peripheral skeletal muscles have been described including atrophy [27,31], reduced myocyte cross-sectional area [27,31], loss of type IIB fibers [27], increased fatigability [32,33], lipofuscin inclusions [33] and increased antioxidant enzyme levels [33]. Thus in EMP, overall skeletal muscle function is altered and therapies with the potential to improve skeletal muscle function may have beneficial effects.…”
Section: Introductionmentioning
confidence: 99%